Perancangan Infografis Songket Lombok - Fadhli Almu’iini Ahda; Fariz Aulia Rahman (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2017)
Lombok Island not only has a stunning natural beauty, Lombok Island also has a special woven cloth area called the songket Lombok. However, there are still many people who do not know the existence of Lombok songket especially the people outside the island of Lombok. But as the development of technology now, information in the form of animated video muchin demand by thepublic because it looks more interesting. There fore information of Lombok songket clothin the form of info graphic video is needed. Infog raphics is a medium thatis used to inform about the beauty of Lombok songket cloth, by using this infographic information will look interesting and easy to understand. The observations were conducted directly in the songket craftsmen in Sukerare and Sade villages. Conducting interviews directly to the craft smanalso playsan important role to know what data are needed. The design of this infographic animation videousing motion graphic technique. This infographic design aims to provide information about Lombok songket clothtolocal and foreign tourists. The design of the concept takes the theme of infographics. This infographic uses images, photos, backsound and also text as support. This animated video was designed using Adobe Illustrator CS6 application to sketch into digital form, Adobe After Effect CS6 to create animated movement, Adobe Audition CS6 to give dubbing. Results from the testto 33 respondents as sampleswere 77. 5%.